2006
DOI: 10.1128/aem.01903-06
|View full text |Cite
|
Sign up to set email alerts
|

Giardia Cysts and Cryptosporidium Oocysts in Membrane-Filtered Municipal Wastewater Used for Irrigation

Abstract: A wastewater tertiary treatment system based on membrane ultrafiltration and fed with secondary-treated municipal wastewater was evaluated for its Giardia cyst and Cryptosporidium oocyst removal efficiency. Giardia duodenalis (assemblages A and B) and Cryptosporidium parvum were identified in feed water but were found in filtered water only during occasional failure of the filtration system.Treated wastewater can be utilized as an alternative water source for agricultural irrigation, but advanced treatment is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
4

Year Published

2010
2010
2016
2016

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 19 publications
2
30
0
4
Order By: Relevance
“…However, our study showed that high concentrations of Giardia (>4 μm) could occur in the MBR effluent caused by membrane integrity failure. Lonigro et al (2006) also found Giardia and Cryptosporidium in filtered water during occasional failure of the ultrafiltration system for treating secondary effluent.…”
Section: Risk Assessment Of Giardiamentioning
confidence: 92%
See 3 more Smart Citations
“…However, our study showed that high concentrations of Giardia (>4 μm) could occur in the MBR effluent caused by membrane integrity failure. Lonigro et al (2006) also found Giardia and Cryptosporidium in filtered water during occasional failure of the ultrafiltration system for treating secondary effluent.…”
Section: Risk Assessment Of Giardiamentioning
confidence: 92%
“…This could cause particular concerns over the release of pathogens when membrane integrity failure occurs, as pathogens may be concentrated in activated sludge in an MBR system. Lonigro et al (2006) also detected Giardia and Cryptosporidium in filtered water from an MBR during occasional failure of the ultrafiltration system for treating secondary effluent. Therefore, it will be of importance to assess the risk of Giardia in MBR effluents when a membrane loses its integrity.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…are transmitted to humans via consumption of contaminated water and food but also by direct contact with infected hosts. A marked increase in the incidence of cryptosporidiosis associated with the contamination of environmental water with human and animal feces has been reported [1][2][3][4][5] , while cases of co-infection with Giardia intestinalis have been also described [6][7][8][9] . The first outbreak of human cryptosporidiosis is reported from United States in 1984, and later from several other countries worldwide [10][11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%